The Deportation Machine : America's Long History of Expelling Immigrants - Goodman, Adam (Historian) (Book collections on Project MUSE., 2020)
"By most accounts, the United States has deported around five million people since 1882-but this includes only what the federal government calls "formal deportations." "Voluntary departures," where undocumented immigrants who have been detained agree to leave within a specified time period, and "self-deportations," where undocumented immigrants leave because legal structures in the United States have made their lives too difficult and frightening, together constitute 90% of the undocumented immigrants who have been expelled by the federal government. This brings the number of deportees to fifty-six million. These forms of deportation rely on threats and coercion created at the federal, state, and local levels, using large-scale publicity campaigns, the fear of immigration raids, and detentions to cost-effectively push people out of the country. Here, Adam Goodman traces a comprehensive history of American deportation policies from 1882 to the present and near future. He shows that some of the country's largest deportation operations expelled hundreds of thousands of people almost exclusively through the use of voluntary departures and through carefully-planned fear campaigns that terrified undocumented immigrants through newspaper, radio, and television publicity. These deportation efforts have disproportionately targeted Mexican immigrants, who make up half of non-citizens but 90% of deportees. Goodman examines the political economy of these deportation operations, arguing that they run on private transportation companies, corrupt public-private relations, and the creation of fear-based internal borders for long-term undocumented residents. He grounds his conclusions in over four years of research in English- and Spanish-language archives and twenty-five oral histories conducted with both immigration officials and immigrants-revealing for the first time the true magnitude and deep historical roots of anti-immigrant policy in the United States"--